THE EFFECTIVENESS OF TEACHING READING IN DESCRIPTIVE TEXT BY USING MIND MAPPING TECHNIQUE FOR THE FIRST YEAR STUDENTS AT MAN KRECEK - Zamruddin, M. (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 9 No 3 (2019): LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
This research is aimed to know the effectiveness of teaching reading in descriptive text by using Mind Mapping Technique at the first year students at MAN Krecek. The research design is quantitative experimental research which is using pretest and posttest as the data collection and the treatment to give the teaching reading by Mind Mapping Technique. The subject of research consisted as 34 students of X class science program 3. The result of study showed the significant difference between pre-test and post-test. By SPSS 16.0 calculation, the mean is 7.647, the standard deviation is 12.928, standard error mean is 2.217, and the result of t-test is 3.449.The sig. 2-tailed shows 0.002. It means that the result is significant in 1% significance level. So it can be conclude that teaching reading in descriptive text by using Mind Mapping Technique at the first year students at MAN Krecek is effective. The result of this study recommended for the teacher to give the suitable technique to teach reading. Then, the content of the study can be reference for the next researcher.